Investigating the Liquid Moisture Transport Behavior of Cotton and Polyester Cotton Blended Woven Fabric - Salma Farooq; Saira Faisal; Fareha Asim (Mehran University Research Journal of Engineering and Technology, 2022)
This study focused on the effects of varying the warp and weft densities and blend ratio on the overall liquid transport behavior of plain woven 100% cotton and polyester/cotton blended fabric. Overall Moisture Management Capability (OMMC) and Accumulative One-way Transport Index (AOTI) along with wetting and spreading time of the top and bottom surfaces was measured on moisture management tester. The results were used as a basis to grade the fabric for its moisture transport behavior. It was observed that polyester/cotton blends have an overall higher accumulative one-way transport index and overall moisture management capability than 100% cotton fabric. Furthermore, an increase in the polyester content in the fabric resulted in a significant increase in the transport of moisture. However less number of warp and weft yarns in the blended fabric improved the overall moisture management capability of the fabric.